Covalent Tethering and Residues with Bulky Hydrophobic Side Chains Enable Self‐Assembly of Distinct Amyloid Structures. (9th November 2016) - Ruiz, Jérémy; Boehringer, Régis; Grogg, Marcel; Raya, Jésus; Schirer, Alicia; Crucifix, Corinne; Hellwig, Petra; Schultz, Patrick; Torbeev, Vladimir
Abstract: Polymorphism is a common property of amyloid fibers that complicates their detailed structural and functional studies. Here we report experiments illustrating the chemical principles that enable the formation of amyloid polymorphs with distinct stoichiometric composition. Using appropriate covalent tethering we programmed self‐assembly of a model peptide corresponding to the [20–41] fragment of human β2‐microglobulin into fibers with either trimeric or dimeric amyloid cores. Using a set of biophysical and biochemical methods we demonstrated their distinct structural, morphological, and templating properties. Furthermore, we showed that supramolecular approaches in which the peptide is modified with bulky substituents can also be applied to modulate the formation of different fiber polymorphs. Such strategies, when applied to disease‐related peptides and proteins, will greatly help in the evaluation of the biological properties of structurally distinct amyloids. Abstract : Amyloids under control : covalent tethering and supramolecular strategies were successfully used to direct the self‐assembly of distinct polymorphs of amyloid fibers. These approaches are potentially useful for the preparation of homogeneous amyloid samples for structural studies and determining the differences in biological activities of amyloid polymorphs.